2009
DOI: 10.1123/rsj.33.2.89
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Job Satisfaction among Campus Recreation Administrators at Four-Year Public and Private Institutions

Abstract: The primary purpose of this study was to investigate aspects of the job that influence job satisfaction among campus recreation administrators. Job satisfaction was measured by the Job Satisfaction Survey (JSS) which consisted of nine subscale measures that relate to employee job satisfaction and strongly examines perceptual and attitudinal variables (Spector, 1997). Participants, consisting of 104 campus recreation administrators, were affiliated with the National Intramural Recreational Sports Association (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 93 publications
(229 reference statements)
1
24
0
2
Order By: Relevance
“…however, a higher level of satisfaction was reported among employees who had more experience within an organization (i.e., loftier job titles) than those who were in lower, entry-level positions. Kaltenbaugh (2009) also investigated job aspects that influenced employment satisfaction among campus recreation professionals and found that the level of supervision and nature of the work were ranked highest among administrators at four-year institutions. While certain features of campus recreation employment have been found to have an effect on job satisfaction, personality as it applies to vocational assessment has yet to be investigated in the context of a COR setting.…”
Section: Conscientiousnessmentioning
confidence: 99%
“…however, a higher level of satisfaction was reported among employees who had more experience within an organization (i.e., loftier job titles) than those who were in lower, entry-level positions. Kaltenbaugh (2009) also investigated job aspects that influenced employment satisfaction among campus recreation professionals and found that the level of supervision and nature of the work were ranked highest among administrators at four-year institutions. While certain features of campus recreation employment have been found to have an effect on job satisfaction, personality as it applies to vocational assessment has yet to be investigated in the context of a COR setting.…”
Section: Conscientiousnessmentioning
confidence: 99%
“…The elements will be examined individually in this section, despite their linkages to each other, for the sake of clarity. 2008;Gummesson, 2002aGummesson, , 2002b. The technological changes of the past thirty years resulted in goods, services, and technology becoming an intertwined entity.…”
Section: Change Agents Driving Total Marketing and Post-brandmentioning
confidence: 99%
“…On recense également quelques études sur la satisfaction au travail des intervenants en loisir, mais oeuvrant en milieux aussi divers que les parcs nationaux (Chung, Jung, Kyle, & Petrick, 2010), les services municipaux (Bartlett & McKinney, 2004;Gladwell et al, 2010;Silverberg, Marshall, & Ellis, 2001), les YMCA (Brown, Yoshioka, & Munoz, 2004;Wallace & Weese, 1995), voire les services universitaires aux étudiants (Kaltenbaugh, 2009;Zhang, DeMichele, & Connaughton, 2004).…”
Section: Satisfaction Au Travailunclassified
“…En milieu universitaire, Zhang et al (2004) ont conclu que les gestionnaires de services de loisirs sont généralement satisfaits de leur environnement de travail, bien que cette satisfaction ne soit pas reliée aux conditions de travail. Enfin, l'enquête menée par Kaltenbaugh (2009), toujours en milieu universitaire, a notamment mis en lumière le taux élevé de satisfaction des spécialistes en loisir, généralement associé à la nature du travail et à la qualité de la supervision.…”
Section: Satisfaction Au Travailunclassified